Evaluation of friction welded bi-material joint strength subjected to impact loads - Shah, Qasim Hussain; Abdullah, Kassim (Trans Tech Publications Ltd., Switzerland, 2011)
In the present work the bond strength of two friction welded polymers was investigated when the bi-material specimens were subjected to projectile impact at 86 ms-1. Two transparent polymer rods of Polycarbonate(PC) and Polymethylmethacrylate Acrylic(PMMA) were joined together using rotary friction welding. Specimens were cut into two different batches. In one batch the central portion of the rod specimens were removed and in the other batch the complete specimens along with their central portion were retained. When the bi-material specimens were subjected to projectile impact the cracks initiated in the comparatively brittle PMMA specimens and were able to propagate across the interface and subsequently into the PC specimen for the first batch of the specimens while the cracks were either arrested at the bi-material interface or the cracks propagated along the interface in the second batch of specimens. From the experimental work it was deduced that the crack propagation along the interface or across the interface could be a good measure of the bond strength difference of a bi-material joined using rotary friction welding process. Weak point of rotary friction welding has also been identified